Anesthesia for fetal operative procedures: A systematic review - Duci, Miriam; Pulvirenti, Rebecca; Fascetti Leon, Francesco; Capolupo, Irma; Veronese, Paola; Gamba, Piergiorgio; Tognon, Costanza (Frontiers in Pain Research, 2022)
Objective The anesthetic management of fetal operative procedures (FOP) is a highly debated topic. Literature on fetal pain perception and response to external stimuli is rapidly expanding. Nonetheless, there is no consensus on the fetal consciousness nor on the instruments to measure pain levels. As a result, no guidelines or clinical recommendations on anesthesia modality during FOP are available. This systematic literature review aimed to collect the available knowledge on the most common fetal interventions, and summarize the reported outcomes for each anesthetic approach. Additional aim was to provide an overall evaluation of the most commonly used anesthetic agents. Methods Two systematic literature searches were performed in Embase, Medline, Web of Science Core Collection and Cochrane Central Register of Controlled Trials up to December 2021. To best cover the available evidence, one literature search was mostly focused on fetal surgical procedures; while anesthesia during FOP was the main target for the second search. The following fetal procedures were included: fetal transfusion, laser ablation of placental anastomosis, twin-reversed arterial perfusion treatment, fetoscopic endoluminal tracheal occlusion, thoraco-amniotic shunt, vesico-amniotic shunt, myelomeningocele repair, resection of sacrococcygeal teratoma, ligation of amniotic bands, balloon valvuloplasty/septoplasty, ex-utero intrapartum treatment, and ovarian cyst resection/aspiration. Yielded articles were screened against the same inclusion criteria. Studies reporting anesthesia details and procedures’ outcomes were considered. Descriptive statistical analysis was performed and findings were reported in a narrative manner. Results The literature searches yielded 1,679 articles, with 429 being selected for full-text evaluation. A total of 168 articles were included. Overall, no significant differences were found among procedures performed under maternal anesthesia or maternal-fetal anesthesia. Procedures requiring invasive fetal manipulation resulted to be more effective when performed under maternal anesthesia only. Based on the available data, a wide range of anesthetic agents are currently deployed and no consistency has been found neither between centers nor procedures. Conclusions This systematic review shows great variance in the anesthetic management during FOP. Further studies, systematically reporting intraoperative fetal monitoring and fetal hormonal responses to external stimuli, are necessary to identify the best anesthetic approach. Additional investigations on pain pathways and fetal pain perception are advisable.